Work-related stress and performance among primary school teachers - Sandra Ingried Asaloei; Agustinus Kia Wolomasi; Basilius Redan Werang (Institute of Advanced Engineering and Science, 2020)
Stress influences teachers’ performance and school effectiveness alike. The main objective of this study is to describe work-related stress and its eventual relationship with job performance of teachers working in primary schools of Boven Digoel district, Indonesia. To attain this objective, a survey study was employed by utilizing two survey questionnaires. Research data derived from a total of 352 primary school teachers who were incidentally established as samples. Data were statistically analyzed using Pearson’s correlation analysis. Result of data analysis shows a significant negative correlation between the work-related stress and job performance of teachers working in the primary schools of Boven Digoel district.